A Numerical Thermal-Hydraulic Model to Simulate the Fast Transients in a Supercritical Water Channel Subjected to Sharp Pressure Variations (Communications in Computational Physics, 2020)
The present work demonstrates the extension of a thermal-hydraulic model,THRUST, with an objective to simulate the fast transient flow dynamics in a supercriticalwater channel of circular cross section. THRUST is a 1-D model which solvesthe nonlinearly coupled mass, axial momentum and energy conservation equationsin time domain based on a characteristics-dependent fully implicit finite differencescheme using an Eulerian approach. The model developed accounts for the compressibilityof the supercritical flow by considering the finite value of acoustic speed in thesolution algorithm and treats the boundary conditions naturally. A supercritical waterchannel of circular cross section, for which the experimental data is available at steadystate operating conditions, is chosen for the transient simulations to start with. Twodifferent case studies are undertaken with a purpose to assess the capability of themodel to analyze the fast transient processes caused by the large reduction in systempressure. The first transient case study is where the initial exit pressure is reduced by1 MPa exponentially in a time span of 5 s. In the second case study, the transient isinitiated with a sudden step decrease in the exit pressure by the same amount. Resultsobtained for both the case studies show the desired performance from the modeldeveloped.